2017
DOI: 10.1088/1758-5090/aa8854
|View full text |Cite
|
Sign up to set email alerts
|

Green bioprinting: extrusion-based fabrication of plant cell-laden biopolymer hydrogel scaffolds

Abstract: Plant cell cultures produce active agents for pharmaceuticals, food and cosmetics. However, up to now process control for plant cell suspension cultures is challenging. A positive impact of cell immobilization, such as encapsulation in hydrogel beads, on secondary metabolites production has been reported for several plant species. The aim of this work was to develop a method for bioprinting of plant cells in order to allow fabrication of free-formed three-dimensional matrices with defined internal pore archite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 30 publications
1
53
0
1
Order By: Relevance
“…Another approach demonstrated that the addition of 0.9% agarose dramatically increased the zero-shear viscosity of a blend of 3% alginate and 3% mc resulting in improved shape fidelity (obtained horizontal macropores did not collapse in scaffolds with 20 layers). 35 In this blend, mc contributed positively by its shear-thinning behaviour, whereas alginate-agarose alone could not be printed. This biopolymer blend was developed for Green Bioprinting with plant cell cultures.…”
Section: Development Of Novel Bioinks Including Methylcellulosementioning
confidence: 89%
See 3 more Smart Citations
“…Another approach demonstrated that the addition of 0.9% agarose dramatically increased the zero-shear viscosity of a blend of 3% alginate and 3% mc resulting in improved shape fidelity (obtained horizontal macropores did not collapse in scaffolds with 20 layers). 35 In this blend, mc contributed positively by its shear-thinning behaviour, whereas alginate-agarose alone could not be printed. This biopolymer blend was developed for Green Bioprinting with plant cell cultures.…”
Section: Development Of Novel Bioinks Including Methylcellulosementioning
confidence: 89%
“…Due to this reason, commercially available mc usually is characterized by its viscosity (of a 2% solution at 20°C) and the molecular weight is a recalculated value, which does not allow drawing conclusions for the distribution of the molecular weight. We found that most studies [32][33][34][35][36][37][38][39][40][41] used an mc with a given viscosity of 4000 mPa s (M n ≈ 86 kDa); 30 these studies have in common to have achieved printing of multiple layers and only limited collapse of predesigned macropores. Other studies 42,43 reported about the use of mc with a given viscosity of 15 mPa s (M n ≈ 14 kDa) and found significant improvements of the printed shape fidelity in presence of mc compared to mc-free controls, but those structures lacked the evidence of multiple layer stacking.…”
Section: Biomaterials Science Minireviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite their promise as bioinks for tissue engineering, further characterization of the toxicological properties, immunogenicity, and in vivo durability of these materials needs to be elucidated to determine their validity over widely used synthetic materials such as polylactic acid and polycaprolactone (Pariente et al, 2001). Many of the plant-based materials are being translated from the food industry, where their bioactivity, rheological properties, and facile gelation have garnered significant interest in bioprinting (Seidel et al, 2017;Vancauwenberghe et al, 2017). However, many of the crosslinking methods, especially those involving high temperatures, harsh chemical conditions and ultraviolet radiation, warrant further adaptation to ensure biocompatibility, and cell viability is preserved if these methods are to be used for tissue bioprinting purposes.…”
Section: Tissue Engineeringmentioning
confidence: 99%